Thrombopoietin is required for full phenotype expression in a JAK2V617F transgenic mouse model of polycythemia vera. - Jerry L Spivak; Akil Merchant; Donna M Williams; Ophelia Rogers; Wanke Zhao; Amy Duffield; Linda S Resar; Alison R Moliterno; Zhizhuang J Zhao (PLoS ONE, 2020)
The myeloproliferative neoplasms, polycythemia vera, essential thrombocytosis and primary myelofibrosis are hematopoietic stem cell disorders and share driver mutations that either directly activate the thrombopoietin receptor, MPL, or activate it indirectly through gain-of-function mutations in the gene for JAK2, its cognate tyrosine kinase. Paradoxically, MPL surface expression in hematopoietic stem cells is also reduced in the myeloproliferative neoplasms due to abnormal post-translational glycosylation and premature destruction of JAK2, suggesting that the myeloproliferative neoplasms are disorders of MPL processing since MPL is the only hematopoietic growth factor receptor in hematopoietic stem cells. To examine this possibility, we genetically manipulated MPL expression and maturation in a JAK2V617F transgenic mouse model of polycythemia vera. Elimination of MPL expression completely abrogated the polycythemia vera phenotype in this JAK2V617F transgenic mouse model, which could only be partially restored by expression of one MPL allele. Most importantly, elimination of thrombopoietin gene expression abrogated the polycythemia vera phenotype in this JAK2V617F transgenic mouse model, which could be completely restored by expression of a single thrombopoietin allele. These data indicate that polycythemia vera is in part a thrombopoietin-dependent disorder and that targeting the MPL-thrombopoietin axis could be an effective, nonmyelotoxic therapeutic strategy in this disorder.